Persuasive Technology 5th International Conference, PERSUASIVE 2010, Copenhagen, Denmark, June 7-10, 2010, Proceedings - Ploug, Thomas; Hasle, Per; Oinas-Kukkonen, Harri (Information Systems and Applications, incl. Internet/Web, and HCI, 2010)
This book constitutes the proceedings of the 5th International Conference on Persuasive Technology, PERSUASIVE 2010, held in Copenhagen Denmark in June 2010. The 25 papers presented were carefully reviewed and selected from 80 submissions. In addition three keynote papers are included in this volume. The topics covered are emotions and user experience, ambient persuasive systems, persuasive design, persuasion profiles, designing for health, psychology of persuasion, embodied and conversational agents, economic incentives, and future directions for persuasive technology.